P2 8 Avoiding Exams To The Extreme - Halliday, Tom; Brough, Oliver J. T.; Gardiner, Corban C. B.; Grout, Joel E. (Physics Special Topics, 2023)
This paper determines the velocities and consequential forces needed to move the Earth to outside of the habitable zone (0.7 AU). A Hohmann transfer is used and requires two changes in velocity, first at 2,700 m/s to achieve an elliptical orbit and second at 2,900 m/s to achieve a closer circular orbit. The forces required are 1.87 x 10^22 N and 1.34 x 10^22 N respectively.